2023
DOI: 10.1111/joa.13929
|View full text |Cite
|
Sign up to set email alerts
|

Cranial morphology of Balkan and West Asian livestock guardian dogs

Abstract: Several large “shepherd” or livestock guardian dog (LGD) breeds were historically selectively bred to protect sheep and goat flocks in the Balkans, Anatolia, and the Caucasus regions. Although these breeds exhibit similar behavior, their morphology is different. Yet, the fine characterization of the phenotypic differences remains to be analyzed. The aim of this study is to characterize cranial morphology in the specific Balkan and West Asian LGD breeds. We use a 3D geometric morphometric in order to assess mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…An alternative method involves calculating the SI by acquiring the 3D coordinate points of landmarks and calculating the cranial length and width in 3D space, a requirement for measuring the SI of a 3D skull model [27,32]. This method has been applied in various studies of geometric morphometry [3,6,30,32,[44][45][46][47][48][49]. However, our study used landmark-based morphometrics focusing on orbital and optic chiasm landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method involves calculating the SI by acquiring the 3D coordinate points of landmarks and calculating the cranial length and width in 3D space, a requirement for measuring the SI of a 3D skull model [27,32]. This method has been applied in various studies of geometric morphometry [3,6,30,32,[44][45][46][47][48][49]. However, our study used landmark-based morphometrics focusing on orbital and optic chiasm landmarks.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting shape data are most commonly reduced in dimensionality through principal component analysis. In recent years, 3D shape analysis has become much more readily available [15][16][17], and landmarking automation has enabled the reliable collection of standardized sets of landmarks [18].…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, many three‐dimensional, radiological and different modelling studies have been carried out on bones. (Baygeldi et al., 2022 ; Demircioğlu et al., 2020 ; Guzel et al., 2022 ; Güzel et al., 2022; Gündemir et al., 2023a ; Gündemir et al., 2023b ; Gündemir et al., 2023c ; Hadžiomerović et al., 2023 ; Yılmaz & Demircioğlu, 2020 ; Yılmaz & Demircioğlu, 2021 ; Szara et al., 2023 ). However, no study has been found that examines the skulls of Romanov sheep in detail.…”
Section: Introductionmentioning
confidence: 99%